Intensification of cellulosic fiber drying through fundamental insights and process modeling. Issue 16 (16th November 2020) - Mondal, Sabyasachi; Dutta, Suvankar; Agarwala, Puja; Nimbalkar, Vishvas; Dhumal, Sunil S.
Abstract: Balance between heat, mass, and momentum transfer decides effectiveness of cellulose fiber drying in a conveyor dryer such as final product moisture variability aspects and steam consumption. High speed murata vortex spinning (MVS) machines demand precise control over cellulosic fiber moisture and its variability during yarn making. In the present study, cellulosic fiber drying operation at commercial scale is intensified by reducing the moisture variability with the help of drying fundamentals (drying rate curve and critical moisture content) along with mass transfer correlation, and ASPEN based process model development. Cellulosic fiber drying follows falling rate period, where rate of mass transfer decreases with moisture content. Established mass transfer correlation provides connect between Sherwood number with process parameters such as air temperature, inlet fiber moisture content, and absolute air humidity. Developed ASPEN process model for commercial scale cellulosic fiber drying was validated successfully with plant data. Deployment of optimized moderate drying strategy derived based on process modeling and drying fundamentals at commercial scale significantly reduced the moisture variability (80% product moisture falls within 10.5–11.5% moisture band on dry basis) with 9% steam consumption reduction.